If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y = 2(10 + -1y) 4y = (10 * 2 + -1y * 2) 4y = (20 + -2y) Solving 4y = 20 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 4y + 2y = 20 + -2y + 2y Combine like terms: 4y + 2y = 6y 6y = 20 + -2y + 2y Combine like terms: -2y + 2y = 0 6y = 20 + 0 6y = 20 Divide each side by '6'. y = 3.333333333 Simplifying y = 3.333333333
| 6x+21=57 | | 8y-6=2y+5 | | 8+n=2 | | 8r^2+2=7r^2 | | 3y=2(10-y) | | 6+9x=38+x | | 6x+3=5x | | 10-2(x-7)=-4 | | 50=2x+12x | | 6-2z=-12 | | 2x+5=29 | | 2x-4=12x-34 | | y+4=x | | 3x^4-6x^2=0 | | 161-2x=25x+20 | | 1.75m+3=12 | | 5x+20=12x-57 | | 6-8x=51-43x | | 3x+9=5x-13 | | -7+(-7)= | | 6.3-.3x=-4.2 | | 3a=-8+a | | 7x-1.8=-4x+0.4 | | X^2-ax-bx-ab=0 | | 9x-41=3x+1 | | -6x-3.9=-7x-4.1 | | 2.3X+10=16 | | 114-4x=3x+9 | | 2-4b=2+3 | | 0.7(x-1)=0.3(x+16) | | -x^2+x+2=0 | | 3x+10=2x |